High-Flying Strategies: An In-depth Examination of Jetstar's Competitive Positioning and Challenges in the New Zealand Aviation Market - Wang, Xingshu (Transactions on Social Science, Education and Humanities Research, 2024)
This research thoroughly examines Jetstar's competitive stance and obstacles in the New Zealand aviation sector as an Australian low-cost carrier. Since its founding in 2003, Qantas Airways subsidiary Jetstar has grown to become one of the biggest low-cost carriers in the Asia-Pacific area. After providing an overview of Jetstar's operations and business, the article delves extensively into the macro environment of the corporation by examining its PESTLE (Political, Economic, Socio-Cultural, Technological, Legal, and Environmental) components. In the meantime, Air New Zealand and Virgin Australia—two of Jetstar's main rivals in the New Zealand market—are the subject of a competitive analysis. The article lists Jetstar's advantages, disadvantages, opportunities, and threats in a SWOT analysis. Finally, based on an in-depth analysis of the key challenges faced by Jetstar, including intense market competition, limited route network, and economic and political risks. In response to the analysed scenario, the article makes some recommendations, including expanding the route network, adopting sustainable practices, and maintaining efficient operations. Ultimately, the research in this article provides strategic guidance for Jetstar in the New Zealand market to optimise its market share, address competitive challenges and enhance customer satisfaction.